Subjek Pemberdayaan Masyarakat dalam Al-Qur'an dan Sunnah - Harahap, Masrul Efendi Umar (Jurnal at-Taghyir, 2020)
Abstract: Public welfare is currently a major problem in various parts of the world, especially in Indonesia, many empowerment programs made by the government to improve peopleâ€Ÿs welfare are not in line with expectations, even causing new problems. Therefore it is necessary to review the nature of community empowerment from a different perspective. In this article the author is interested in examining the nature of community empowerment in Al-Quran and Sunnah which is seen from the four characteristics of empowerment namely, empowerment that is fardiyah, jamâ€™iah, umaraâ€™ and isolated communities by using literature studies and sociological approaches that are following the concept of community empowerment. The results of this study are, firstly the term empowerment in Al-Quran and Sunnah is in line with daâ€Ÿwah, the culprit is referred to as daâ€Ÿi and the action is referred to as â€œamar maâ€™ruf nahi munkarâ€ which is equally inviting people to change for a better approach individual. The second empowerment in the form of organization/institution and government is called jamâ€™iyah which means a group of people who have the power to make the right decision with consideration of the benefit of the community. Thirdly an empowering agent is called umaraâ€™ who is demanded to be able to carry out his duties and maintain the mandate entrusted to him, the four isolated communities are the main objects of empowerment activities, preachers or perpetrators must have special abilities that can find appropriate solutions to overcome problems and be able to develop the potential of the community.Keyword: Subject of Empowerment, Al-Qurâ€Ÿan, and SunnahAbstrak: Kesejahteraan masyarakat saat ini menjadi masalah utama diberbagai belahan dunia khususnya di Indonesia, banyak program-program pemberdayaan yang dibuat oleh pemerintah dengan tujuan meningkatkan kesejahteraan masyarakat tidak sesuai dengan harapan, bahkan malah menimbulkan masalah baru. Oleh sebab itu perlu mengkaji kembali hakikat pemberdayaan masyarakat dari sudut pandang yang berbeda. Didalam artikel ini penulis tertarik untuk mengkaji hakikat pemberdayaan masyarakat dalam Al-Quran dan Sunnah yang dilihat dari empat sifat pemberdayaan yaitu, pemberdayaan yang bersifat fardiyah, jamâ€Ÿiah, umara dan masyarakat terisolir dengan menggunakan kajian pustaka dan pendekatan sosiologis yang sesuai dengan konsep pemberdayaan masyarakat. Adapun hasil dari kajian ini yaitu, pertama istilah pemberdayaan di dalam Al-Quran dan Sunnah sejalan dengan dakwah, pelakunya disebut sebagai daâ€™i dan aksinya disebut sebagai amar maâ€™ruf nahi munkar yaitu samasama mengajak manusia kepada perubahan yang lebih baik dengan pendekatan individual, kedua pemberdayaan dalam bentuk organisasi/lembaga dan pemerintahan disebut jamâ€™iyah yang memiliki arti sekumpulan orang yang memiliki kuasa membuat sebuah keputusan yang tepat dengan pertimbangan kemaslahatan masyarakat, ketiga seorang pelaku pemberdaya disebut sebagai umaraâ€Ÿ yang dituntut mampu menjalankan tugas dan menjaga amanah yang dititipkan terhadapnya, keempat masyarakat terisolir merupakan objek utama dari kegiatan pemberdayaan, daâ€™i atau pelaku pemberdayanya harus memiliki kemampuan khusus yang mampu mencarikan solusi-solusi tepat dalam mengatasi masalah serta mampu mengembangkan potensi-potensi yang dimiliki masyarakat.Key word: Subject of Empowerment, Al-Qurâ€Ÿan and Sunnah